Targeting the Tumor Microenvironment: A Close Up of Tumor-Associated Macrophages and Neutrophils - Russo, Massimo; Nastasi, Claudia (Frontiers in Oncology, 2022)
The importance of the tumor microenvironment (TME) in dynamically regulating cancer progression and influencing the therapeutic outcome is widely accepted and appreciated. Several therapeutic strategies to modify or modulate the TME, like angiogenesis or immune checkpoint inhibitors, showed clinical efficacy and received approval from regulatory authorities. Within recent decades, new promising strategies targeting myeloid cells have been implemented in preclinical cancer models. The predominance of specific cell phenotypes in the TME has been attributed to pro- or anti-tumoral. Hence, their modulation can, in turn, alter the responses to standard-of-care treatments, making them more or less effective. Here, we summarize and discuss the current knowledge and the correlated challenges about the tumor-associated macrophages and neutrophils targeting strategies, current treatments, and future developments.